DESCRIPTION OF THE WORDIN THE WORKS OF ALISHER NAVOIY (Scientific journal of the Fergana State University, 2023)
In the works of Nizamiddin Mir Alisher Navoi, the classification of the scientific and artistic definition and interpretations of the word, the incomparable place and importanceof the word in our life, which is a very beautiful and beautiful language (speech) unit, is replaced by the poet`s thinking. Analysis from a specific linguistic and artistic point of view is the main goal of this article. In the article, an indepth study of the word and its logical possibilities explained in the works of Alisher Navoi, appreciationof the word as a unique and divine blessing, the conditions of national growth in the developmentof New Uzbekistan and the result of scientific research on our ianguage, is the main factor determining our future is emphasized. Alisher Navoi, the firest world linguist, emphasized the distinction between language and speech phenomena, the limitless possibilities of the word as a linguistic and artistic unit of speech, its unique functions in the artistic reflection of life, and the beginning of all existence in the conclusions of Alisher Navoi`s thought. It will be analyzed.